Angiogenesis and its modulation in the pathophysiology and treatment of endometrial carcinoma - Craig A. Mayr; Dennis Yi-Shin Kuo; Gary L. Goldberg; June Yijuan Hou (Frontiers Media S.A., 2011)
Endometrial cancer is the most common gynecologic malignancy in women. When detected early, this disease has a relatively good prognosis. However, advanced stage disease is associated with a poor outcome. Current therapies for advanced endometrial cancer include surgery, chemotherapy, radiotherapy, and hormonal therapy. Responses to these modalities are variable, but rarely exceed 20%. Angiogenesis plays a critical role in both the normal and the pathologic physiology of the human endometrium. Like a wide array of other tumors, the formation of new blood vessels to feed an enlarging tumor mass occurs in endometrial cancer. This review focuses on the role of angiogenesis and its inhibition in the pathophysiology and treatment of endometrial cancer.